2000
DOI: 10.1177/004051750007000904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot Water Processing on Dyeing and Mechanical Properties of Cottons Treated with Liquid Ammonia and Sodium Hydroxide

Abstract: NH3 and NaOH/NH3 treated cotton fabrics are processed with hot water at 100 and 130°C, and excellent shrink resistance is obtained with the processing. The crystallite form is transformed from cellulose III to cellulose I. Crystallinity decreased by the NH3 treatment increases a little after hot water processing and washing shrinkage is considerably controlled. Although the dyeing rate decreases with the NH 3 treatment, it increases a little with subsequent hot water processing. In contrast, equilibrium dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…We expected that an increase of the equilibrium dye uptake of the silk fabric with the acid dyes would correspond to an increase in the active amino group of the silk fabric available for dyeing because of the relaxation of the amorphous region by the treatments. In a previous study,2, 10, 11 we reported that liquid ammonia treatment of the cottons induced a considerable decreases in crystallinity, nevertheless the apparent dyeing rate with Direct Blue 1 was controlled a little compared with that of the untreated fabric. However, the equilibrium dye uptake of the liquid ammonia treated cottons increased more than the untreated.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…We expected that an increase of the equilibrium dye uptake of the silk fabric with the acid dyes would correspond to an increase in the active amino group of the silk fabric available for dyeing because of the relaxation of the amorphous region by the treatments. In a previous study,2, 10, 11 we reported that liquid ammonia treatment of the cottons induced a considerable decreases in crystallinity, nevertheless the apparent dyeing rate with Direct Blue 1 was controlled a little compared with that of the untreated fabric. However, the equilibrium dye uptake of the liquid ammonia treated cottons increased more than the untreated.…”
Section: Resultsmentioning
confidence: 83%
“…Liquid ammonia treatment has been practically done in textile finishing since 20 years ago, and is been carried out as a pretreatment of the shape stability and for improving the soft hand of cotton fabric. The liquid ammonia treatment of cottons caused a decrease of the apparent dyeing rate comparing with the mercerization despite a considerable decrease in the crystallinity 1–3. The liquid ammonia treatment is not always effective in increasing the dyeing rate not only for the cellulosic fiber,2, 4, 5 but also for the nylon 6 fiber.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mercerisation at high temperature is now a well-established method [13]. e penetration of caustic soda into the bre structure is more rapid [14], which ensures more uniform treatment but less swelling [8]. is in turn enhances lustre without a ecting the strength of the bre.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid ammonia treatment has already been practically processed for cotton fabric [1][2][3][4][5]. We, before now, studied the effect of the treatment on fine structure of the cellulosic fibers in relation to the dyeing and KES mechanical properties [4,5]. Recently, ammonia-gas treatment of the cellulosic, wool, and silk fabrics was done [6][7][8][9].…”
Section: Introducti Introducti Introducti Introduction On On Onmentioning
confidence: 99%